Longitudinal follow‐up and performance validation of an mRNA‐based urine test (Xpert® Bladder Cancer Monitor ) for surveillance in patients with non‐muscle‐invasive bladder cancer. (5th May 2021) - Cowan, Barrett; Klein, Eric; Jansz, Ken; Westenfelder, Karl; Bradford, Timothy; Peterson, Chad; Scherr, Douglas; Karsh, Lawrence I.; Egerdie, Blair; Witjes, Alfred; Trainer, Andrew; Harris, Richard; et al.
Abstract : Objective: To evaluate the performance of the Xpert Bladder Cancer Monitor (Xpert; Cepheid, Sunnyvale, CA, USA) test as a predictor of tumour recurrence in patients with non‐muscle‐invasive bladder cancer (NMIBC). Patients and Methods: Patients ( n = 429) undergoing surveillance for NMIBC underwent Xpert, cytology, and UroVysion testing. Patients with a positive Xpert and a negative cystoscopy result (positive‐negative [PN] group, n = 66) and a control group of double negative patients (negative Xpert and cystoscopy results [NN] group) were followed for 12 months (±90 days). Results: Histology‐confirmed recurrences were detected in 58 patients (13.5%). Xpert had an overall sensitivity of 60.3% and a specificity of 76.5%. The sensitivity for high‐grade (HG) cancer was 87% with a negative predictive value (NPV) of 99%. Urine cytology showed an overall sensitivity of 23.2% (47.6% sensitivity for HG tumours) and a specificity of 88.3%. In the PN group, 32% ( n = 21) developed a recurrence within 12 months, 11 of which were HG tumours. In the NN control group, 14% ( n = 9) developed a recurrence and only two were HG tumours. The hazard ratio for developing recurrence in the PN group was 2.68 for all tumours and 6.84 for HG cancer. Conclusions: The Xpert test has a high sensitivity for detecting the recurrence of cancer and a high NPV for excluding HG cancer. In addition, the data suggest that patients with a positive Xpert assay in the setting of negative cystoscopy are at high risk for recurrence and need close surveillance.